Towards integrative machine learning and knowledge extraction : BIRS Workshop, Banff, AB, Canada, July 24-26, 2015, Revised selected papers /: BIRS Workshop, Banff, AB, Canada, July 24-26, 2015, Revised selected papers. (2017) - Unknown
No abstract available